2023
DOI: 10.1002/smll.202207240
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Electrochemical Catalysis and Nonenzymatic Sensing Toward Glucose by Single‐Atom Pt Supported on Cu@CuO Core–Shell Nanowires

Abstract: Diabetes Federation. [3] For quick patient screening and medical monitoring, it is crucial to develop fast and accurate sensors for glucose detection. [4] The commercial glucose sensors are electrochemical enzymatic based, but they have limitations, such as susceptible to deterioration from environmental influence (pH, temperature, and humidity) and poor stability due to inactivation of enzymes. [5] Therefore, electrochemical nonenzymatic glucose sensors have received increasing attention for the next-generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Density functional theory (DFT) calculations were employed to gain further insights into the superior electrocatalytic reactivity of LIG-TiO 2 –Pt toward H 2 O 2 . Previous literature reported that the binding energy of H 2 O 2 (Δ E *) on a catalyst’s surface can be utilized to evaluate its sensing performance toward an H 2 O 2 sensor. , Hereof, the corresponding adsorption sites of H 2 O 2 on LIG-TiO 2 , LIG-Pt, and LIG-TiO 2 –Pt are shown in Figure G, indicating that the active sites are Ti, Pt, and Ti–Pt atoms, respectively. The charge density difference and Bader charge analysis (Figure H,I) point out that the Pt nanoparticle anchored on the TiO 2 surface loses more electrons (0.223 e – ), indicating a strong electronic interaction between the Pt and TiO 2 nanoparticles.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Density functional theory (DFT) calculations were employed to gain further insights into the superior electrocatalytic reactivity of LIG-TiO 2 –Pt toward H 2 O 2 . Previous literature reported that the binding energy of H 2 O 2 (Δ E *) on a catalyst’s surface can be utilized to evaluate its sensing performance toward an H 2 O 2 sensor. , Hereof, the corresponding adsorption sites of H 2 O 2 on LIG-TiO 2 , LIG-Pt, and LIG-TiO 2 –Pt are shown in Figure G, indicating that the active sites are Ti, Pt, and Ti–Pt atoms, respectively. The charge density difference and Bader charge analysis (Figure H,I) point out that the Pt nanoparticle anchored on the TiO 2 surface loses more electrons (0.223 e – ), indicating a strong electronic interaction between the Pt and TiO 2 nanoparticles.…”
Section: Resultsmentioning
confidence: 89%
“…Pt (14.14 × 10 −4 S cm −1 ) exhibits a faster electron conduction capacity, which highly aligns with the abovementioned CV, EIS, i−t, and ECSA results (Figure2F).Density functional theory (DFT) calculations were employed to gain further insights into the superior electrocatalytic reactivity of LIG-TiO 2 −Pt toward H 2 O 2 . Previous literature reported that the binding energy of H 2 O 2 (ΔE*) on a catalyst's surface can be utilized to evaluate its sensing performance toward an H 2 O 2 sensor 39,40. Hereof, the corresponding adsorption sites ofH 2 O 2 on LIG-TiO 2 , LIG-Pt, and LIG-TiO 2 −Pt are shown in Figure 2G, indicating that the active sites are Ti, Pt, and Ti−Pt atoms, respectively.…”
mentioning
confidence: 99%
“…In a few years, single-atom nanozymes have been emerging as a flashpoint for research due to their abundant and atomically dispersed individual active metal atoms, which can show excellent natural enzyme activity. Notably, SAzymes, as an emerging-efficient nanozyme, have been designed to catalog the electrochemical procedures of certain substrates, thus generating electrically hypersensitive galvanic signals . Thus, these advanced SAzymes-based electrochemical biosensors have succeeded in creating the quantitative assays for certain targets. , Qin et al successfully constructed a kind of PEC signaling platform for sensitivity detection of acetylcholinesterase activity and organophosphorus pesticides by utilizing the oxygen-reducing and peroxidase-like activities of Fe SACs.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the noble metal (Ag, Pt, Au, Pd, etc.) functionalization [24,25] can induce electronic and catalytic effects to greatly enhance the sensing properties of ZnO to detect TEA. The noble metals will provide a large number of active sites for the adsorption and dissociation of oxygen molecules.…”
Section: Introductionmentioning
confidence: 99%